Learning disabilities: analysis of 69 children - Meister Eduardo Kaehler; Bruck Isac; Antoniuk Sérgio Antônio; Crippa Ana Chrystina de Souza; Muzzolon Sandra Regina Baggio; Spessatto Adriane; Gregolin Reni (Arquivos de Neuro-Psiquiatria)
With this article we intend to demonstrate the importance of evaluation and follow up of children with learning disabilities, through a multidisciplinary team. As well as to establish the need of intervention. We evaluate 69 children, from Aline Picheth Public School, in Curitiba, attending first or second grade of elementary school, through general and evolutionary neurological examination, pediatric checklist symptoms, and social, linguistic and psychological (WISC-III, Bender Infantile and WPPSI-figures) evaluation. The incidence was higher in boys (84,1%), familiar history of learning disabilities was found in 42%, and writing abnormalities in 56,5%. The most frequent diagnosis was attention deficit and hyperactivity disorder, in 39,1%. With this program, we aimed to reduce the retention taxes and stress the importance of this evaluation, and, if necessary, multidisciplinar intervention in the cases of learning disabilities.